Role of Transesophageal Echocardiography Among Patients With Atrial Fibrillation Undergoing Electrophysiology Testing - Priester, Rory; Bunting, Troy; Usher, Bruce; Chiaramida, Salvatore; Taylor, Marian H.; Gregg, David; Sturdivant, J. Lacy; Leman, Robert B.; Wharton, J. Marcus; Gold, Michael R. (The American journal of cardiology, 2009)
External or internal shocks administered to terminate ventricular arrhythmias as a part of electrophysiology or implantable cardioverter-defibrillator testing, can inadvertently cardiovert atrial fibrillation (AF). Moreover, anticoagulation therapy is often withheld in these patients in anticipation of an invasive procedure. The risk of embolic events during these procedures has not been well described. Accordingly, the present study was a prospective evaluation of the incidence of left atrial (LA) thrombus and AF cardioversion among patients undergoing ventricular arrhythmia assessment. Transesophageal echocardiography was routinely performed on 44 consecutive patients in AF with subtherapeutic anticoagulation undergoing electrophysiology or implantable cardioverter-defibrillator testing. Arrhythmia induction was not performed when LA thrombus was present. The incidence and clinical predictors of thrombus, the inadvertent cardioversion of AF, and adverse events related to the procedure were assessed during the subsequent 4 to 6 weeks. Left atrial thrombus was observed in 12 patients (27%). Sinus rhythm was restored in 29 patients (91%), at least transiently, who underwent testing with a shock delivered. No adverse neurologic or hemorrhagic complications were observed. Univariate analysis identified no predictors of LA thrombus or cardioversion to sinus rhythm. In conclusion, LA thrombus and cardioversion to sinus rhythm are common among patients with AF undergoing an evaluation of ventricular arrhythmias. Transesophageal echocardiography performed before the procedure in patients with subtherapeutic anticoagulation is warranted to minimize embolic complications. This strategy appears to be a safe method to guide diagnostic testing in this patient population.